Critical review of the current and future prospects of VEGF-TKIs in the management of squamous cell carcinoma of head and neck - Puttagunta, Prashant; Pamulapati, Saagar V.; Bates, James E.; Gross, Jennifer H.; Stokes, William A.; Schmitt, Nicole C.; Steuer, Conor; Teng, Yong; Saba, Nabil F. (Frontiers in Oncology, 2023)
As the prognosis for squamous cell carcinoma of the head and neck remains unsatisfactory when compared to other malignancies, novel therapies targeting specific biomarkers are a critical emerging area of great promise. One particular class of drugs that has been developed to impede tumor angiogenesis is vascular endothelial growth factor-tyrosine kinase inhibitors. As current data is primarily limited to preclinical and phase I/II trials, this review summarizes the current and future prospects of these agents in squamous cell carcinoma of the head and neck. In particular, the combination of these agents with immunotherapy is an exciting area that may be a promising option for patients with recurrent or metastatic disease, evidenced in recent trials such as the combination immune checkpoint inhibitors with lenvatinib and cabozantinib. In addition,